2011
DOI: 10.7819/rbgn.v13i40.922
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Six Sigma by the 500 Largent Companies in Portugal

Abstract: The Six Sigma had its genesis in big industrial companies that have implemented it as a tool for reducing defects. The initial success encouraged its application in other areas and we see today successful implementation in other sectors such as services, and within their own organizations in other areas beyond production, setting; this has contributed to Six Sigma being recognized as a new management model. In order to determine the extent to which Six Sigma is present in Portuguese companies, a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Cabrita and de Vaz (2008) examined the inter-relationships among intellectual capital components within Portuguese banks and found that intellectual capital was an important driver of organisational value in these banks. da Conceição and Major (2011) looked at the impact of adoption of Six Sigma on organisational performance of Portuguese companies and found gains in productivity and greater customer satisfaction. de Sena et al (2013) evaluated the effects of the ISO 9001 quality certification process on the business performance of Portuguese organisations and found mixed and inconclusive results.…”
Section: High Performance In Portugalmentioning
confidence: 99%
“…Cabrita and de Vaz (2008) examined the inter-relationships among intellectual capital components within Portuguese banks and found that intellectual capital was an important driver of organisational value in these banks. da Conceição and Major (2011) looked at the impact of adoption of Six Sigma on organisational performance of Portuguese companies and found gains in productivity and greater customer satisfaction. de Sena et al (2013) evaluated the effects of the ISO 9001 quality certification process on the business performance of Portuguese organisations and found mixed and inconclusive results.…”
Section: High Performance In Portugalmentioning
confidence: 99%
“…From the 124 questionnaires received and validated, only 13 of the companies indicated to have adopted Six Sigma. Conceição and Major (2011) conducted a survey to determine the extent to which Six Sigma is adopted by the largest 500 non-financial companies operating in Portugal. Their main conclusions were the following:…”
Section: Six Sigma In Portugalmentioning
confidence: 99%